# Solve for z 8(2z-8)-2=8(z-5)+6 8(2z-8)-2=8(z-5)+6
Simplify 8(2z-8)-2.
Simplify each term.
Apply the distributive property.
8(2z)+8⋅-8-2=8(z-5)+6
Multiply 2 by 8.
16z+8⋅-8-2=8(z-5)+6
Multiply 8 by -8.
16z-64-2=8(z-5)+6
16z-64-2=8(z-5)+6
Subtract 2 from -64.
16z-66=8(z-5)+6
16z-66=8(z-5)+6
Simplify 8(z-5)+6.
Simplify each term.
Apply the distributive property.
16z-66=8z+8⋅-5+6
Multiply 8 by -5.
16z-66=8z-40+6
16z-66=8z-40+6
Add -40 and 6.
16z-66=8z-34
16z-66=8z-34
Move all terms containing z to the left side of the equation.
Subtract 8z from both sides of the equation.
16z-66-8z=-34
Subtract 8z from 16z.
8z-66=-34
8z-66=-34
Move all terms not containing z to the right side of the equation.
Add 66 to both sides of the equation.
8z=-34+66
Add -34 and 66.
8z=32
8z=32
Divide each term by 8 and simplify.
Divide each term in 8z=32 by 8.
8z8=328
Cancel the common factor of 8.
Cancel the common factor.
8z8=328
Divide z by 1.
z=328
z=328
Divide 32 by 8.
z=4
z=4
Solve for z 8(2z-8)-2=8(z-5)+6

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top